MODERN TECHNOLOGIES OF DISTANCE PREPARATION OF TEACHERS OF POSTGRADUATE MEDICAL EDUCATION - Mintser, O. P.; Babintseva, L. Yu. (Medical Informatics and Engineering, 2020)
Background. Issues of development of postgraduate medical education of scientific and pedagogical workers became relevant in connection with the modernization of the entire education system. The state lacks a holistic system of training and retraining of teachers of postgraduate medical education. Materials and methods. Results. The aim of the study is to substantiation of the system of purposeful and program efforts to ensure the traditional orientation of the development of pedagogical and scientific-pedagogical workers on the improvement of postgraduate medical teaching with the use of a systematic approach. It is emphasized that the training of pedagogical and scientific-pedagogical workers in the system of postgraduate medical education in the period of intensive reform of the industry becomes extremely important. Conclusion. A special training program is proposed as part of the strategy of systemic continuous pedagogical development. An important indicator of a special program can be an indicator of personal development of the teacher—a vector characteristic with coordinates in the form of digital indicators of the level of competencies, knowledge, skills and social activity.